Exploring the Potential of Orthosiphon Stamineus: A Literature Review - Muliana GH (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The objective of this study is to investigate the potential health benefits of Orthosiphon stamineus, with a particular focus on the kumis kucing plant (Orthosiphon stamineus). This study employs a literature review as its research methodology. The findings of the research were used to gather information on the benefits of Orthosiphon stamineus, also known as kumis kucing. These benefits include its use as a therapeutic agent for gout, a treatment for dental caries, an immunomodulator, an anticancer agent, a neuroprotective agent, and a diuretic for urinary stones. It has been demonstrated to possess antibacterial properties against both Pseudomonas aeruginosa and Aeromonas hydrophylla, as well as antibiotic properties against gonorrhea. Additionally, it has been shown to act as an anthelmintic against Ascaris suum worms, a antiviral against herpes simplex type I, an antidiabetic, an anti-obesity agent, a treatment for rheumatism, a heart health enhancer, and a gastroprotective agent. It is anticipated that these findings will inform the development of novel products that harness the medicinal properties of the Orthosiphon stamineus plant.